2017
DOI: 10.1111/jam.13475
|View full text |Cite
|
Sign up to set email alerts
|

Increased propionate concentration inLactobacillus mucosae-fermented wet brewers grains and duringin vitrorumen fermentation

Abstract: The presented research provided the identification of L. mucosae 521129 as a propionate producer and was metabolically profiled. Furthermore, data present the putative application of this organism in improving the fermentation of wet brewers grains and in vitro rumen fermentation. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…The rumen epithelium is responsible for many important physiological functions including absorption, transport, and SCFA metabolism [37,63]. In this study, we found that higher concentrations of butyrate was produced following treatment with 10 6 CFU/ml C. saccharobutylicum, indicating an increase in the carbon and energy sources for fatty acid synthesis [64]. Several studies had demonstrated that treatment with butyrateproducing bacteria resulted in enhanced butyrate production.…”
mentioning
confidence: 51%
“…The rumen epithelium is responsible for many important physiological functions including absorption, transport, and SCFA metabolism [37,63]. In this study, we found that higher concentrations of butyrate was produced following treatment with 10 6 CFU/ml C. saccharobutylicum, indicating an increase in the carbon and energy sources for fatty acid synthesis [64]. Several studies had demonstrated that treatment with butyrateproducing bacteria resulted in enhanced butyrate production.…”
mentioning
confidence: 51%
“…In addition, higher relative abundance of Lactobacillus was detected under RES, which could also contribute to the higher molar proportion of propionate. A study suggested that an increased in vitro propionate production was associated with the growth of Lactobacillus mucosae (Mamuad et al , 2017). Molar proportion of butyrate was not different between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A gas ow regulator was then opened to allow gas ow inside a syringe barrel and the plunger was subsequently pulled gradually until the pressure reading on the machine display was zero. The volume of gas trapped inside the barrel was recorded as the total gas produced [49,52].…”
Section: Methodsmentioning
confidence: 99%